Effectiveness of abdominal electroacupuncture therapy for poststroke constipation: a meta-analysis - Zhao, Xiuzhen; Liu, Linxi; Diao, Yingxiu; Ma, Chunling (Frontiers in Neurology, 2024)
BackgroundElectroacupuncture (EA) has been employed to address the symptoms of constipation in individuals who have experienced a stroke. However, supporting evidence for its efficacy is lacking. This meta-analysis aims to investigate whether EA was effective in treating poststroke constipation.MethodsWe conducted a comprehensive search of eight databases, including four English-language databases (PubMed, Embase, Web of Science, and the Cochrane Library) and four Chinese-language databases (Chinese Biomedical Literature Database, China National Knowledge Infrastructure, VIP, and Wanfang), for randomized controlled trials (RCTs) published from inception through January 31, 2023. To assess treatment effectiveness, we calculated the risk ratio (RR) or mean difference (MD) with 95% confidence interval (CI).ResultsA total of 9 RCTs involving 601 participants were included. No heterogeneity was found across the included RCTs. The results of this meta-analysis indicated significant improvements in the total effective rate (RR = 1.39, 95% CI 1.27, 1.52), cure rates (RR 1.87, 95% CI 1.38, 2.54), constipation scoring system (MD = −2.51, 95% CI −3.05, −1.97), and quality of life (MD = −10.69, 95% CI −14.2, −7.17) in the EA group compared with the control group.ConclusionCurrent evidence indicates that EA may be recommended for patients experiencing poststroke constipation. The lack of thorough investigations has undermined the quality of the major findings.